The clinical value of FAPI PET/CT in delineating target volumes for nasopharyngeal carcinoma. - Xu, Wansu; Zou, Yihe; Zhang, Yang; Lv, Qiyuan; Deng, Xia; Li, Kejie; Zhang, Xuemei; Wang, Junhui; Yu, Wenliang; Xie, Raoying; Su, Meng; He, Huijuan; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: To evaluate the efficacy of 18F-AIF-NOTA-FAPI-04 PET/CT in improving the accuracy of target volume delineation in nasopharyngeal carcinoma (NPC). Methods: Automatic delineation of the primary tumor target volume was conducted for 21 newly diagnosed NPC patients using 18F-AIF-NOTA-FAPI-04 PET/CT images, which applied a threshold-based segmentation with 5% increments from 20 to 60% of SUVmax. Manual delineation of the primary tumor was performed on MRI images. The study analyzed the gross target volumes (GTV) discrepancies between 18F-AIF-NOTA-FAPI-04 PET/CT and MRI. Furthermore, we compared how the two imaging modalities affected the assessment of the primary tumors' involvement of bone-related structures and soft tissue (mucosa) infiltration. Results: There were variations in the primary tumor target volume across the different imaging methods. There were no significant differences observed between GTV-FAPI 20%, GTV-FAPI 25%, and GTV-FAPI 30% compared to GTV-MRI. Among them, GTV-FAPI 20% showed the closest similarity to GTV-MRI. 18F-AIF-NOTA-FAPI-04 PET/CT was superior to MRI in detecting soft tissue and bone tissue involvement in primary tumors. Conclusions: 18F-AIF-NOTA-FAPI-04 PET/CT enhances precision in delineating GTV for NPC and demonstrates clinical utility in T-staging.